The Role of Brand Trust, Brand Image, Brand Equity on Repurchase Intention - Sutanto, Wullyatri Dewi Risma; Kussudyarsana, Kussudyarsana (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In the rapidly growing business world, companies are faced with intense competition due to the emergence of new companies. This research analyzes the role of brand trust, brand image and brand equity on repurchase intention of Wardah brand cosmetics. The aim of this research is to determine brand trust, brand image and brand equity on repurchase intentions. This research uses quantitative analysis with purposive sampling technique. The population of this study were FEB students at Muhammadiyah University, Surkarta who had purchased Wardah cosmetics with a sample of 192 respondents. The data collection technique uses a questionnaire with a standardized Likert scale using SPSS version 26. The analytical method used in this research is multiple linear regression analysis using several variables, namely brand trust, brand image, brand equity and repurchase intention. The results of this research show that brand trust has a significant effect on repurchase intentions, brand image has a positive and significant effect on repurchase intentions, brand equity has a significant effect on repurchase intentions. This is proven by F sig. 0.000 is smaller than 0.05. The R Square value of 0.982 indicates that the ability of the brand trust model (X1), brand image (X2), brand equity (X3) explains the variation in the repurchase intention variable (Y) by 98.2% and the remainder is influenced by other independent variables by 1.8 %.